Cavitation flow and broadband noise source characteristics of NACA66 hydrofoil with a V groove on the suction surface. (15th December 2022) - Jia, Jiahao; Zhang, Jinsong; Huang, Zhenwei
Abstract: In the present work, a V groove on the suction surface is proposed to investigate the cavitation flow and noise sources of a NACA66 hydrofoil. The SST k - ω turbulence model and broadband noise source model is employed to analyze the flow pattern and noise distribution. Proper orthogonal decomposition (POD) is then used to investigate the coherent structure of cavitation flow around the hydrofoil. The results show that, under cloud cavitation conditions, the groove improves the energy characteristics of the hydrofoil and increases the lift-to-drag ratio by 2.95%. During the sheet cavitation growth phase, the groove can suppress the development of low-pressure, low-velocity regions on the hydrofoil surface, thus suppressing cavitation near the leading edge of the hydrofoil. During the cavitation collapse stage, the groove reduces the pressure impact of cavitation collapse on the hydrofoil. The groove extends a cavitation cycle and reduces the average cavitation volume during a cavitation cycle by 17.46%. Results indicate that during a cavitation cycle, the groove reduces the average dipole noise on the hydrofoil surface by 5.07% and the average quadrupole noise on the middle longitudinal section by 6.86%. POD results show that the first five orders of the modes capture more than 90% of the energy of the flow field. The primary frequency of the modal coefficients of Mode 1 and Mode 2 is the cavitation frequency, and the other frequencies are multiples of the cavitation frequency. The groove significantly affects Mode 2, which represents a change in velocity distribution in the flow field characteristics. Highlights: A V groove on the suction surface is proposed to investigate the cavitation flow and noise sources of hydrofoil. Proper orthogonal decomposition is used to investigate the coherent structure of cavitation flow. During the cavitation collapse stage, the groove reduces the pressure impact of cavitation collapse on the hydrofoil. The groove extends a cavitation cycle and reduces the average cavitation volume. The primary frequency of the modal coefficients of Mode 1 and Mode 2 is the cavitation frequency.